The Influence of Public Service Management Policy and Organizational Culture on Work Performance with Service Quality as a Mediating Variable - Haikal, Fikri; Nurbaiti, Nurbaiti; Nurlaila, Nurlaila (Image : Jurnal Riset Manajemen, 2023)
The objective of this research is to examine and analyze: (1) the impact of public service management policies on Service Quality, (2) the effect of organizational culture on Service Quality, (3) the relationship between Service Quality and work performance, (4) how public service management policies affect work performance through Service Quality, and (5) the influence of organizational culture on work performance via Service Quality. A quantitative approach was employed, utilizing a questionnaire for data collection. The study focused on the entire population of Medan Police Traffic Units involved in SIM management, totaling 45 informants, using a saturated sampling technique. Path Analysis was the analytical technique applied, facilitated by SmartPLS The analysis involved assessments of the outer model, mediation tests, and inner models. Findings from the field revealed the following: (1) The Public Service Management Policy positively and significantly impacts Service Quality, reflected by a coefficient of 0.778 and a p-value of 0.000; (2) Organizational culture has a negative yet insignificant effect on Service Quality, indicated by a coefficient of -0.021 and a p-value of 0.920; (3) Service Quality has a significant positive effect on work performance, with a coefficient of 0.770 and a p-value of 0.000; (4) Service Quality serves as an effective mediator in the relationship between Public Service Management Policy and work performance; however, (5) it does not mediate the influence of organizational culture on performance.